Reimagining Peter Pan: The Postmodern Childhood Portrayal in Wendy (2020) - Dhita Hapsarani; Nadia Farah Lutfiputri (k@ta: A Biannual Publication on the Study of Languange and Literature, 2021)
As a social construct, the view towards childhood remains to change over time. Literary works, such as films or novels from different periods of time which feature children's characters as the protagonists can be the right medium to identify those shifts. This article analyzes Wendy (2020) film as the latest adaptation of J.M. Barrie’s classic children's novel Peter Pan (1911). This film has made some transformations from the original novel to make the story more relevant in today’s context, including how it showcases childhood that is experienced by the children’s characters. Using textual and comparative analysis, this study attempts to see the transformations in the film adaptation and how it shows a different childhood construction from the one appearing in the source novel. Referring to the concept of postmodern childhood, Linda Hutcheon’s adaptation theory, and Bordwell and Thompson’s elements of film analysis, this study reveals how Wendy (2020) has exemplified the concept of postmodern childhood through the portrayal of children’s roles, children’s agency, and children-adults relationship.